2021
DOI: 10.26603/001c.19452
|View full text |Cite
|
Sign up to set email alerts
|

A Preseason Training Program With the Nordic Hamstring Exercise Increases Eccentric Knee Flexor Strength and Fascicle Length in Professional Female Soccer Players

Abstract: Background Training programs that include the Nordic hamstring exercise (NHE) have been shown to increase eccentric knee flexor strength and biceps femoris fascicle length in male athletes. However, the effect of NHE on female athletes remains unknown. Purpose To investigate the collective and individual responses of professional female soccer players engaged in a preseason training program with the NHE regarding eccentric knee flexor strength and biceps femoris long he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 42 publications
1
7
1
Order By: Relevance
“…Few studies have investigated the response to using the Nordic hamstring exercise among female football players, and only one has measured strength with a device that resembles the NordBord. Seventeen female elite players performing a high-volume Nordic hamstring programme during the preseason (8 weeks, 472 total reps) increased their hamstring strength by 13% [19], which is similar to the 10% and 13% increase we observed in our high-and low-volume groups, respectively. Our results are lower than the ∼20% increase found after Nordic hamstring interventions among male athletes [31,35] and the ∼30% increase seen among recreationally active men [24,30].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Few studies have investigated the response to using the Nordic hamstring exercise among female football players, and only one has measured strength with a device that resembles the NordBord. Seventeen female elite players performing a high-volume Nordic hamstring programme during the preseason (8 weeks, 472 total reps) increased their hamstring strength by 13% [19], which is similar to the 10% and 13% increase we observed in our high-and low-volume groups, respectively. Our results are lower than the ∼20% increase found after Nordic hamstring interventions among male athletes [31,35] and the ∼30% increase seen among recreationally active men [24,30].…”
Section: Discussionsupporting
confidence: 84%
“…As we do not have a control group, the improvements in strength can potentially be caused by football training and not the Nordic hamstrings training. We consider this unlikely, as amateur players tested 8 weeks apart did not change their eccentric hamstring force, when training football only [ 19 ]. However, football training may have contributed to some of the reported muscle soreness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study revealed a correlation between calf girth and distant kick. Meanwhile, the mean calf girth in this study is less than the value reported [3,29].…”
Section: Discussioncontrasting
confidence: 90%
“…In the included studies, a total of four experiments from three articles [26,27,29] investigated the effect of NHE on BFLH fascicle length, with a combined sample size of 54 and 52 for the experimental and control groups, respectively. Heterogeneity tests were performed, and the results were shown in Figure 9, showing no heterogeneity between the combined studies (I2=0%, P=0.57), so a xed-effects model was used to calculate the combined effect size.…”
Section: Effect Of Nhe On Bflh Fascicle Lengthmentioning
confidence: 99%